1997
DOI: 10.1002/clc.4960200415
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of asymptomatic valvar pulmonary stenosis diagnosed in infancy

Abstract: SummaryBackground and hypothesis: Valvar pulmonary stenosis is a common congenital heart defect. Progression of stenosis over time, even when mild initially, has been shown by serial cardiac catheterization studies in children and adults. We studied the natural history of asymptomatic valvar pulmonary stenosis diagnosed in infancy with two-dimensional echocardiography and Doppler method.Method.v: Between November 1986 and March 1993,51 infants in the Northeast Tennessee and Southwest Virginia region were clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Few of these 5,7 show an unfavorable evolution of the mild defect, due to the rapid worsening of the condition, similar to what is observed in more severe defects, mainly when exteriorizing occurs early in life. Mody 5 observed that the increase of defect severity was noticed in patients younger than 1 year, even those who presented mild effects, at a faster progression rate than in patients older than 1 year of age.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Few of these 5,7 show an unfavorable evolution of the mild defect, due to the rapid worsening of the condition, similar to what is observed in more severe defects, mainly when exteriorizing occurs early in life. Mody 5 observed that the increase of defect severity was noticed in patients younger than 1 year, even those who presented mild effects, at a faster progression rate than in patients older than 1 year of age.…”
Section: Discussionsupporting
confidence: 53%
“…The knowledge of the natural history of pulmonary valve stenosis allows us to state that moderate and accentuated defects tend to undergo the intensifying of their effects 2,3 and the mild defects, their decrease [2][3][4][5][6][7][8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations